ENT 530 Social Media Report : Muscle Matrix / Muhammad Hadil Muhammad Razali - Muhammad Razali, Muhammad Hadil (2021)
“MUSCLE MATRIX” is an online based entrepreneurship that sells protein powder.I chose this brand and product because I want to promote a healthy fitness lifestyle and also because I am also a regular user of this product. I applied as a MUSCLE MATRIX dropshipper from an advertisement from an Fcebook account as they need dropshippers and agents. I had Mr Qanda who guides me on the details and information about the products. The dropshipcommission is RM20 for each bottle sold. I choose to operate my business by social media which is making Facebook with a page (‘Protein Monster’ with URL link created https://www.facebook.com/Protein-Monster-103176248372476/ .